Lipid Profile and Fasting Blood Sugar Analysis in Patients with Cholelithiasis - Rajaa N.Al-Atrakchey; Mohammed A.Taher; Ibtehal N.Saeed (College of Pharmacy University of Baghdad, 2017)
Cholelithiasis is one of the commonest surgical problems and one of the most common gastrointestinal diseases throughout the world but its pathogenesis remains unclear. Many theories have been proposed forward to explain the mechanism of stone formation. It is not fully clear if symptomatic gallstone disease is associated with a specific pattern of some biochemical abnormalities, as lipid profile and fasting blood sugar in serum of patients. This study was designed to estimate lipid profile and fasting blood sugar in the sera of patients with cholelithiasis in comparison with normal individuals (control). In this study, 104(male=16, female=88) were symptomatic gallstone patients (aged 42.79Â± 12.18 years), and 38(male=6 and female=32) were apparently healthy controls (aged 40.03Â± 7.47 years). Blood samples were collected from symptomatic gallstones patients before their cholecystectomy operation. Over night fasting, blood samples were collected from all subjects to evaluate serum lipid profile: Total cholesterol (TC), triglyceride (TG), high density lipoprotein-cholesterol (HDL-c), low density lipoprotein-cholesterol (LDL-c), very low density lipoprotein-cholesterol (VLDL-c) and fasting serum glucose (FSG). There was a significant increase (P<0.05) in serum: TC, TG, LDL-c, VLDL-c and FSG of patients with cholelithiasis compared to the apparently healthy controls. The study also showed  that there was a significant decrease (P<0.05) in serum HDL-c in gallstone patients compared to control. In conclusion, cholelithiasis was associated with lipid profile and fasting serum glucose abnormality that be the cause or the effect of gallstone formation. These findings should be taken into consideration while treating gallstone patients. Key words: Gallstones, Cholesterol, Cholecystectomy.